Descriptive study on oral health and pathologies in vulnerable migrant adolescents from North and West Africa - Elena Sirumal; Susell Parra-Rojas; Juliana Cassol-Spanemberg; Ana Isabel Contreras-Madrid; David Pérez-Jorge; Rocío Trinidad Velázquez-Cayón (Scientific Reports)
Abstract This descriptive study focuses on the oral health of African migrants, especially adolescents, arriving in the Canary Islands. Notably, these patients show a high prevalence of caries and oral mucosal alterations. These are influenced by multifactorial factors, such as living conditions in their country of origin, hygiene habits, and sugar-rich diets. Furthermore, it is worth noting the need for inclusive oral health policies in receiving countries and the need to develop oral health care protocols in regions with migratory flows to effectively address oral health needs and facilitate the integration of migrants. We included 104 migrant patients from different African countries, mainly from North and West Africa, and analyzed their oral health status. We found that 89.4% of the patients had dental caries, with a higher prevalence in North Africa. Moreover, 25% of patients showed oral mucosal alterations, with leukoedema being the most common condition. Regarding malocclusions, 42.6% of patients had Class I malocclusion and only 15.4% had dental crowding. Regarding intraosseous lesions, 97.1% of the patients had no lesions and most did not require dental prostheses. This study provides a detailed overview of the oral health conditions of African migrants in the Canary Islands.